Non-motor symptoms groups in Parkinson's disease patients : results of a pilot, exploratory study - Pérez Lloret, Santiago (2011)
Fil: Pérez Lloret, Santiago. Hospital y Universidad Paul Sabatier. Departamento de Farmacología Clínica y Neurociencias; Francia